Sosialisasi Pengenalan Teknologi Informasi Beserta Manfaat dan Bahayanya di SDN 1 Banturejo - Helmi Noor Hafidz; Alifah Shofia Fuadah; Amirah Salsabila S.F.D; Ashri Shabrina Afrah (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2023)
In this era of rapid technological development, Information Technology (IT) needs to be taught at all levels of education, including at the elementary school level. The introduction of Information Technology at SDN 1 Banturejo was carried out by holding Information Technology socialization which was held on Saturday, January 7 2023 at 08.00-11.00 WIB. Participants in this activity were students in grades 4 and 5 of SDN 1 Banturejo, totaling 46 students. This activity includes presentation of material, games, and mentoring as well as practice using Microsoft Word and Canva. The method used is a survey technique with test instruments in the form of pre-test and post-test. From the pre-test results, 84% of them did not know the dangers and benefits of information technology, 82% did not know about the Microsoft Word application, and 78% did not know about the Canva application. Meanwhile, from the results of the post-test after the socialization, almost all students at SDN 1 Banturejo already know the dangers and benefits of information technology and how to use Microsoft Word and Canva.